A Case of Myomatous Erythrocytosis Syndrome Associated with a Large Uterine Leiomyoma - Yosuke Ono; Takao Hidaka; Kaori Fukuta; Keiko Kouchi; Kuniaki Yasoshima; Kiyoshi Takagawa; Takashi Arai (Case Reports in Obstetrics and Gynecology)
Several etiologies have been proposed for erythrocytosis associated with uterine leiomyoma. We report a case of erythrocytosis associated with a large uterine leiomyoma, in which specific immunostaining for erythropoietin was positive. A 55-year-old woman, gravida 0, para 0, was referred to our hospital for treatment for a large uterine myoma and erythrocytosis. She had no vaginal bleeding after she reached menopause at 50 years old. She had severe polycythemia: hemoglobin (Hb), 19.9 g/dL; red blood cell count (RBC), 6.65 × 106/mm3; hematocrit, (Hct) 59.1%. An abdominal simple hysterectomy was performed, and a pathological examination confirmed the diagnosis of leiomyoma of the uterus. In addition, immunostaining demonstrated that the cytoplasm of the leiomyoma cells was strongly positive for erythropoietin. After the operation, the patient’s hemoglobin and hematocrit levels normalized, and we diagnosed her condition as myomatous erythrocytosis syndrome.